Exome-Wide Meta-Analysis Identifies Rare 3′-UTR Variant in ERCC1/CD3EAP Associated with Symptoms of Sleep Apnea - van der Spek, Ashley; Luik, Annemarie I.; Kocevska, Desana; Liu, Chunyu; Brouwer, Rutger W. W.; van Rooij, Jeroen G. J.; van den Hout, Mirjam C. G. N.; Kraaij, Robert; Hofman, Albert; Uitterlinden, André G.; van IJcken, Wilfred F. J.; Gottlieb, Daniel J.; et al. (Frontiers in Genetics, 2017)
Obstructive sleep apnea (OSA) is a common sleep breathing disorder associated with an increased risk of cardiovascular and cerebrovascular diseases and mortality. Although OSA is fairly heritable (~40%), there have been only few studies looking into the genetics of OSA. In the present study, we aimed to identify genetic variants associated with symptoms of sleep apnea by performing a whole-exome sequence meta-analysis of symptoms of sleep apnea in 1,475 individuals of European descent. We identified 17 rare genetic variants with at least suggestive evidence of significance. Replication in an independent dataset confirmed the association of a rare genetic variant (rs2229918; minor allele frequency = 0.3%) with symptoms of sleep apnea (p-valuemeta = 6.98×10-9, βmeta = 0.99). Rs2229918 overlaps with the 3’ untranslated regions of ERCC1 and CD3EAP genes on chromosome 19q13. Both genes are expressed in tissues in the neck area, such as the tongue, muscles, cartilage and the trachea. Further, CD3EAP is localized in the nucleus and mitochondria and involved in the tumor necrosis factor-alpha/nuclear factor kappa B signaling pathway. Our results and biological functions of CD3EAP/ERCC1 genes suggest that the 19q13 locus is interesting for further OSA research.